Design and development of seedling transplanter, part 3 - design of plough system and in-charge of design consolidation - Yeo, Chong Peng (2014)
Agri-Food and Veterinary Authority (AVA) has approached Nanyang Technological University (NTU) to design and develop a seedling transplanter, in order to improve the "Seed Plugs" method for the local Singapore farm. The main objectives are to reduce the manpower requirement and improve seedling planting productivity.